On bandwidth maximization of fixed-geometry arrays through convex programming. Issue 5 (23rd March 2020) - Bui, L. T. P.; Anselmi, N.; Isernia, T.; Rocca, P.; Morabito, A. F.
ABSTRACT: We propose a new approach to solve the problem of optimal power synthesis of array antennas, so that maximum possible bandwidth can be granted to fixed sidelobe-level performances. The proposed approach can be applied to any kind of fixed-geometry array that radiates pencil beams and to linear equispaced arrays that generate shaped patterns. The designing problem is cast as a sequence of Convex Programming optimizations. Numerous numerical experiments, including full-wave synthesis of realistic antennas, were carried out and their results discussed here to assess the array antennas' capability of achieving ultra-wideband performances.